Elucidating the Effects of Interconnecting Layer Thickness and Bandgap Variations on the Performance of Monolithic Perovskite/Silicon Tandem Solar Cell by wxAMPS - Mohamad I.S.; Doroody C.; Alkharasani W.M.; Norizan M.N.; Chelvanathan P.; Shahahmadi S.A.; Amin N. (MDPI, 2024)
In this study, we investigated the pathways for integration of perovskite and silicon solar cells through variation of the properties of the interconnecting layer (ICL). The user-friendly computer simulation software wxAMPS was used to conduct the investigation. The simulation started with numerical inspection of the individual single junction sub-cell, and this was followed by performing an electrical and optical evaluation of monolithic 2T tandem PSC/Si, with variation of the thickness and bandgap of the interconnecting layer. The electrical performance of the monolithic crystalline silicon and CH3NH3PbI3 perovskite tandem configuration was observed to be the best with the insertion of a 50 nm thick (Eg ? 2.25 eV) interconnecting layer, which directly contributed to the optimum optical absorption coverage. These design parameters improved the optical absorption and current matching, while also enhancing the electrical performance of the tandem solar cell, which benefited the photovoltaic aspects through lowering the parasitic loss. 2023 by the authors.